Preserving Heritage in the Modern Era: an Analysis of Cultural Value Integration in the Representation of Traditional Chinese Dance Education - Qian, Xiangyun; Saearani, Muhammad Fazli Taib (Jurnal Multidisiplin Sahombu, 2025)
This study explores the representation and integration of cultural values in traditional Chinese dance education through a comprehensive analysis of curriculum documents, arts education policies, and instructional materials. In the context of modernization and globalization, dance education faces critical challenges in preserving the depth of cultural meaning amid growing emphasis on performativity and competitive orientation. Employing a systematic literature review and document analysis, this research assesses the extent to which cultural values—including historical, philosophical, and socio-cultural dimensions—are embedded within the dance education system. Findings indicate that, despite notable integration efforts, the representation of cultural values remains limited and is often marginalized by a predominant focus on technical and aesthetic aspects. Key obstacles include resistance to pedagogical innovation and the dominance of performance-driven paradigms. Nonetheless, the study identifies innovative potential through interdisciplinary approaches and the utilization of digital technologies, which can revitalize the teaching and learning of traditional dance in a contextually relevant and adaptive manner. The pedagogical implications of effectively integrating cultural values include the reinforcement of students’ cultural awareness and identity, and the sustainable preservation of intangible cultural heritage. This research recommends the development of a holistic curriculum, the empowerment of educators, and cross-disciplinary collaboration as key strategies to enhance the role of traditional dance education in cultural preservation and the formation of a national identity aligned with contemporary developments.